Exquisite disturbance attenuation control for a rotary inverted pendulum. (February 2018) - He, Shuaipeng; Zhang, Chuanlin; Yang, Ning; Li, Hui
This paper investigates the problem of active disturbance attenuation control for a rotary inverted pendulum system. A nonlinear disturbance observer is first constructed to estimate the lumped disturbances, and then a feedback domination technique is integrated to handle the nonlinearities in a novel step-by-step way. Hence an exquisite composite controller can be constructed with strong robustness while the nominal control performance can be maintained. By utilizing a recursive stability analysis based on a Lyapunov function, the effectiveness of the proposed controller is assured. Numerical simulation results demonstrate the effectiveness of the proposed algorithm.